2009
DOI: 10.1088/0953-8984/21/9/095008
|View full text |Cite
|
Sign up to set email alerts
|

Relative stability of low-index V2O5surfaces: a density functional investigation

Abstract: Ab initio density functional calculations of the structural and electronic properties of V(2)O(5) bulk and its low-index surfaces are presented. For the bulk oxide and the (010) surface (the natural cleavage plane) a good agreement with experiment and with earlier ab initio calculations is found. For the first time, the investigations are extended to other low-index surfaces: (001) and (100). On both surfaces, termination conserving a bulk-like stoichiometry is preferred, but-in contrast to the (010) surface-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
54
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 41 publications
12
54
1
Order By: Relevance
“…[5][6][7][8][9][10][11][12] The in-plane lattice parameters, in the present paper called a and b ͑but in parts of the literature called a and c͒, are found to be close to the experimental values. [8][9][10][11][12][13] Ganduglia-Pirovano and Sauer 12 carried out GGA calculations using PW91 ͑Ref. 45͒ with PAW, emphasizing convergence and accuracy.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11][12] The in-plane lattice parameters, in the present paper called a and b ͑but in parts of the literature called a and c͒, are found to be close to the experimental values. [8][9][10][11][12][13] Ganduglia-Pirovano and Sauer 12 carried out GGA calculations using PW91 ͑Ref. 45͒ with PAW, emphasizing convergence and accuracy.…”
Section: Resultssupporting
confidence: 82%
“…1 In recent years V 2 O 5 has also been used with intercalating Li ions for high-capacity solid-state batteries. [2][3][4][5] The applied research and industrial focus on catalysis and batteries involving V 2 O 5 has led to a substantial amount of atomic-scale theory studies focusing on the V 2 O 5 bulk [5][6][7][8][9][10][11][12] and its surfaces. [12][13][14][15][16] The bulk of V 2 O 5 has a stacked structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the V 2 O 5 (100) netplane the ''t1'' termination, which is characterized by unsaturated V atoms together with two kinds of oxygen sites (O(1) and O(2)), has been chosen as the most stable from among four possible cuts of this surface [44] (Fig. 2b) were performed.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Also MD (Molecular Dynamic) simulations (based on electrostatic interactions) of the thermal stability of the V 2 O 5 structure have indicated the (010) netplane as the most stable among the three low-index surfaces of V 2 O 5 [43]. Theoretical investigations of the stability of (100) and (001) netplanes perpendicular to the (010) surface [44] have also shown that although their steadiness is an order of magnitude lower, their content in the structure of a standard crystal reaches 7.2 and 8.3%, respectively. For this reason, they should not be neglected.…”
Section: Introductionmentioning
confidence: 99%